Direct spectroscopic characterization of a transitory dirhodium donor-acceptor carbene complex - Kornecki, Katherine P; Briones, John F; Boyarskikh, Vyacheslav; Fullilove, Felicia; Autschbach, Jochen; Schrote, Kaitlin E; Lancaster, Kyle M; Davies, Huw M L; Berry, John F (Science (American Association for the Advancement of Science), 2013)
A multitude of organic transformations catalyzed by dirhodium(II) (Rh2) complexes are thought to proceed via the intermediacy of highly reactive, electrophilic carbenoid intermediates that have eluded direct observation. Herein, we report the generation of a metastable Rh2-carbenoid intermediate supported by a donor-acceptor carbene fragment. This intermediate is stable for a period of ~20 hours in chloroform solution at 0°C, allowing for an exploration of its physical and chemical properties. The Rh=C bond, characterized by vibrational and nuclear magnetic resonance spectroscopy, extended x-ray absorption fine structure analysis, and quantum-chemical calculations, has weak σ and π components. This intermediate performs stoichiometric cyclopropanation and C-H functionalization reactions to give products that are identical to those obtained from analogous Rh2 catalysis.